From Homer to Redi: Some historical notes about the problem of necrophagous blowflies' reproduction - Papavero, Nelson; Pujol-Luz, José Roberto; Teixeira, Dante Martins (Arquivos de Zoologia, 2010)
Some historical notes about the ideas of the reproduction of necrophagous blowflies are presented, including Homer's Iliad, Ancient Egypt and Near East, the Persian Vendidad, William Shakespeare and the elegant experiments of Francesco Redi, who discredited the theory of spontaneous generation.